Unravelling the effect of SrTiO3 antiferrodistortive phase transition on the magnetic properties of La0.7Sr0.3MnO3 thin films - Mota, D. A.
Epitaxial La0.7Sr0.3MnO3 (LSMO) thin films, with different thicknesses ranging from 20 to 330 nm, were deposited on (1 0 0)-oriented strontium titanate (STO) substrates by pulsed laser deposition, with their structure and morphology characterized at room temperature. The magnetic and electric transport properties of the as-processed thin films reveal an abnormal behaviour in the temperature dependent magnetization M(T) below the antiferrodistortive STO phase transition (T-STO), and also an anomaly in the magnetoresistance and electrical resistivity close to the same temperature. Films with thickness <= 100 nm show an in-excess magnetization and pronounced changes in the coercivity due to the interface-mediated magnetoelastic coupling with antiferrodistortive domain wall movement occurring below T-STO. However, in thicker LSMO thin films, an in-defect magnetization is observed. This reversed behaviour can be understood with the emergence in the upper layer of the film, of a columnar structure needed to relax the elastic energy stored in the film, which leads to randomly oriented magnetic domain reconstructions. For enough high-applied magnetic fields, as thermodynamic equilibrium is reached, a full suppression of the anomalous magnetization occurs, wherein the temperature dependence of the magnetization starts to follow the expected Brillouin behaviour.